O referencial ético-humanista nos cursos de graduação em enfermagem de Goiânia-GO - LIMA, Juliana de Oliveira Roque e (2009)
The National Curriculum Guidelines for Undergraduate Courses in Nursing (DCN / ENF) say that the Higher Education Institutions (HEIs) to ensure the students a training that values the ethical and humanistic dimensions, so that he develops attitudes and values oriented to citizenship and solidarity. This study aimed to examine the implementation of the ethical and humanistic reference inserted in the DCN / ENF in the HEI n Nursing in Goiânia, identify and describe the integration of ethical and humanistic reference in the training of nurses in the Pedagogic Curricular Projects PCP of undergraduate nursing courses in Goiânia, check with the teachers of these courses, as they incorporate into their teaching practices, the implementation process of the DCN / ENF regarding ethical and humanistic reference, consider the advantages and difficulties encountered in the implementation of the DCN / ENF, for reference to the ethical and humanist. This descriptive and exploratory study of qualitative approach, was developed in five HEIs in Goiânia that have Undergraduate Courses in Nursing. The data were collected through desk research of the PCP, individual interview with the coordinators of the courses and some teachers of each institution. The data that emerged from the analysis of the PCP and the interviews were submitted to analysis given the guidelines of Bogdan and Biklen (1994). The careful reading of PCP also identified the following categories of coding: ethical, humanist, solidarity, interpersonal relationship, valorization and integrality. These were grouped in two categories: "The training of professional ethical-humanist" and "The focus of the entire context of the Pedagogic Curricular Projects," whose analysis identify relevant issues on ethical and human reference in the PCP in the institutions studied, how: the concern to train their students in accordance with this approach and the importance given by the HEIin the care of their students fully and train them so that they see their clients in full. The coordinates reported the construction process of the PCP and the facilities and difficulties to build and implement the same. However, the construction process did not happen the same way in all HEIs. Different teaching practices for the implementation of ethical and humanistic reference were informed by teachers, and facilities and the difficulties were related to students, the teachers themselves and the institution. Thus, the path is still long way to changes that are necessary, based on the views of those involved in the process. We suggest further studies in this area, in order to stimulate ideas and proposals for the realization of the ethical and humanistic reference in the training of nurses.